The Dynamics of Probiotics on Growth Performance and Immune Response in Broilers - Kabir, S.M.L.; Rahman, M.M.; Rahman, M.B.; Rahman, M.M.; Ahmed, S.U. (International Journal of Poultry Science, 2004)
The research work was conducted on "Hubbard Isa Starbro" broilers to evaluate the dynamics of probiotics relating to live weight gain, carcass yield, weight of cut up meat parts and immune response. Day old broiler chicks were divided into four groups as group A (Vaccinated probiotics fed group), B (Nonvaccinated probiotics fed group), C (Vaccinated conventional fed group) and D (Nonvaccinated conventional fed group). Groups C and D were taken as control birds fed with commercial ration and groups A and B as experimental birds were fed with commercial ration with the addition of 2gm probiotics (Protexin® Boost)/10 litres drinking water upto 6th week of age. The result evidenced the following information: (a) The live weight gains obtained were significantly (p<0.01) higher in experimental birds as compared to control ones at all levels during the period of 2nd, 4th, 5th and 6th weeks of age, both in vaccinated and nonvaccinated birds. (b) A significantly (p<0.01) higher carcass yield occurred in broiler chicks fed with the probiotics on the 2nd, 4th and 6th week of age both in vaccinated and nonvaccinated birds. The weight of leg was found significantly (p<0.01) greater for experimental birds as compared to control ones on the 2nd, 4th and 6th week of age. A significantly (p<0.01) higher breast weight in broiler chicks fed with the probiotics was observed on the 4th and 6th week of age. Analogously a significantly (p<0.05) higher breast portion weight was found in experimental birds as compared to control ones during 2nd week of age. (c) The antibody production was found significantly (p<0.01) higher in experimental birds as compared to control ones. Significant differences were also observed in the weight of spleen and bursa due to probiotics supplementation. The results of the study thus revealed that probiotics supplementation promoted significant influence on live weight gain, high carcass yield, prominent cut up meat parts and immune response.